Perspektif Hukum Islam Tentang Akad Sewa Menyewa Jasa Pacak Kucing - Wulandari, Nur; Susanti, Susi; Pridilla, Utari (Fakultas Syariah IAIN Kerinci, 2022)
This study aims to look at the review of Islamic law on the implementation of cat pacak services at Miaw Cat Shop in Sungai Penuh City, there are several requirements that must be met before pacak is carried out, namely, female cats must be clean and healthy, do not have mold on their skin and cats are really in heat. The approach used is qualitative research with the type of field research. The results of the study found that the Islamic legal review of cat tracking explicitly the apostle Saw., prohibits trading male animal sperm in any form. This is also in line with the hadith, which allows the proceeds from the transaction to be used for the benefit of the people. The opinion of the scholars on the lease of cat breeding is that if a person or community rents or borrows a male for a certain period, then this is not prohibited as it is allowed to rent to mate dates. Meanwhile, according to Imam Syafii, it is said that it is permissible to rent males for a certain period, according to him.